Wine Polyphenols Influence On The Oxidative Stress In Experimental Atheromatosis - Irina Anca Cotea; Irina Esanu; Rodica Ghiuri (Romanian Society of Oral Rehabilitation, 2009)
Starting from the protective properties of the phenol compounds present in wine, signalled out in the case of cardiovascular affections, the sanguine level of some enzymatic and non-enzymatic markers of oxidative stress has been studied on three batch of rabbits subjected to an atherogeneous hypercholesterolemia diet, namely: B1 - untreated, B2 - treated with white wine (2.5 mg/kg body), B3 - treated with red wine (2.5 mg/kg body), comparatively with a control bath (C), subjected to a normal diet. The atherogeneous diet alterates the oxidative anti-stress factors, inducing inhibition of superoxide dismutase (SOD), stimulating glutathion peroxidase (GSH-Px), diminishing the level of reduced glutathion (GSH) and increasing the level of malonil dialdehyde (MDA), comparatively with the values of the control batch. In the wine treated batches, a tendency of normalization of the values of these parameters is observed, along-with a reduction in the level of lipid peroxidation. The melioration effects of anti-oxidation defence are more pronounced in treatments with red wine, comparatively with the white one as due to a richer content of polyphenols, the anti-oxidation capacity of which is well-known, and of scavenger versus the free oxygen radicals, which supports the beneficial effects of a moderate wine consumption.